2017
DOI: 10.1073/pnas.1710828115
|View full text |Cite
|
Sign up to set email alerts
|

Platelet integrins exhibit anisotropic mechanosensing and harness piconewton forces to mediate platelet aggregation

Abstract: Platelet aggregation at the site of vascular injury is essential in clotting. During this process, platelets are bridged by soluble fibrinogen that binds surface integrin receptors. One mystery in the mechanism of platelet aggregation pertains to how resting platelets ignore soluble fibrinogen, the third most abundant protein in the bloodstream, and yet avidly bind immobile fibrinogen on the surface of other platelets at the primary injury site. We speculate that platelet integrins are mechanosensors that test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 43 publications
12
123
0
Order By: Relevance
“…These three contractile phenotypes are not directly congruent with the well-known platelet phenotypes defined by α-/δ-granule secretion or PS exposure (van der Meijden and Heemskerk 2019). On one hand, more than one biochemical phenotype has low contractility, such as resting but also PS positive platelets (Zhang et al 2018;Nechipurenko et al 2019;Agbani et al 2015). On the other hand, little is known about the contractility of platelets that have or have not undergone degranulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These three contractile phenotypes are not directly congruent with the well-known platelet phenotypes defined by α-/δ-granule secretion or PS exposure (van der Meijden and Heemskerk 2019). On one hand, more than one biochemical phenotype has low contractility, such as resting but also PS positive platelets (Zhang et al 2018;Nechipurenko et al 2019;Agbani et al 2015). On the other hand, little is known about the contractility of platelets that have or have not undergone degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet kindlin 3 equally promotes integrin β1 and β3 clustering (Malinin et al 2009) and talin binds either integrin, ruling out a deficiency for a specific adaptor protein for α5β1 in the myeloid lineage (Humphries et al 2009). With ~1'500 copies per cell (Zeiler, Moser, and Mann 2014) and a typical average force of ~5 pN per integrin (Zhang et al 2018), all α5β1 integrins together could only sustain 7.5 nN over prolonged time. This suggests that α5β1 integrins on platelets are merely outcompeted by the abundant αIIbβ3 during Fn fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C) Time lapse images of a spreading human platelet and associated integrin tension signal. Reproduced with permission . Copyright 2018, National Academy of Sciences, USA.…”
Section: Dna‐based Force Probes To Map Piconewton Forces Within Cellsmentioning
confidence: 99%
“…This hairpin force probe technology was recently adapted to investigate the spatiotemporal distribution of integrin forces during platelet activation, which is a key initial event in blood clotting. We found that platelets used their α II b β3 ‐integrins to generate two populations of force patterns: a central zone with integrin forces >19 pN and a ring of peripheral forces along the lamellipodial edge with the magnitudes between 4.7 and 13.1 pN (Figure C).…”
Section: Dna‐based Force Probes To Map Piconewton Forces Within Cellsmentioning
confidence: 99%